Biopharmaceutical analysis of the interaction of L-thyroxin, diclofenac sodium and chondroitin sulphate as components of pharmacotherapy of osteoarthritis manifestations resulted from hypothyroidism. - Nosivets, D. S. (Medicni Perspektivi, 2019)
The article deals with the issue of the biopharmaceutical interaction of L-thyroxin, diclofenac sodium and chondroitin sulfate as components of pharmacotherapy of osteoarthritis manifestations with concomitant hypothyroidism. It is known that functional insufficiency of the thyroid gland has a negative effect on all types of metabolism and in particular on the condition of the bone and cartilage tissue, leading to the development of osteoarthritis. Existing pharmacotherapeutic approaches to the medical treatment of this pathology require the use of basic hormone replacement therapy for the correction of thyroid insufficiency, and NSAIDs as drugs for the symptomatic treatment of osteoarthritis. However, to date, questions of the biopharmaceutical interaction of L-thyroxin and diclofenac sodium are not covered, and the prevention of osteoarthritis against the background of hypothyroidism with the help of chondroitin sulfate and its interaction with the components of pharmacotherapy has not been sufficiently studied. Based on the conducted research, it was established that, proceeding from the theoretical analysis of the physicochemical and chemical properties of these drugs, predominantly reversible acid-base interactions are assumed. The probability of strong and irreversible physicochemical reactions is very low and the physical mixtures of these drugs are not subject to negative interactions which can lead to profound destructive changes on the part of the dosage forms. Since L-thyroxin, diclofenac sodium and chondroitin sulfate are absorbed mainly by simple diffusion, have different transport mechanisms through biological membranes, have different degrees of binding to plasma proteins and various enzyme systems involved in their metabolism and excretion, pharmacokinetic interactions between them are excluded. At the level of pharmacological interaction, the combined and unidirectional effects of the combination of active substances L-thyroxin, diclofenac sodium and chondroitin sulfate are expected, in particular, in degenerative-dystrophic disorders due to functional insufficiency of the thyroid gland, for restoration of the structure of cartilage tissue and for a complex etiotropic and symptomatic treatment of osteoarthritis and related states.